Impaired cell viability and mitochondrial respiration by disperse textile dyes - Lizette M. Cortes; Nelson R. Vinueza; Nelson R. Vinueza (Frontiers in Allergy)
In recent years, the use of synthetic textile dyes has increased. The effects of these chemicals or their metabolites on our skin and our immune system have not been well studied. However, skin irritants have been reported to break the dermal barrier to start a chain of reactions that dysregulate the immune system. In the last decades, the incidence of atopic diseases and cancer has been increasing. There is an urgent need to identify the environmental triggers that fuel these conditions. This study aimed to investigate the effects of some of the common disperse textile dyes on the viability, and mitochondrial function of cultures of mouse keratinocytes (MPEK-BL6 line) and intestinal porcine epithelial cells (IPEC-J2 cells). The cells were cultured with Disperse (D) dyes Red 11, Orange 37, Blue 1, Blue 124, Blue 291, Blue 79.1, and Brown 1 as well as Quinone and Tartrazine, and PPD as control. At concentrations representative of human exposure from 30 min to 3 days. Cell viability, Oxygen Consumption Rate (OCR) and Extracellular Acidification Rate (ECAR) were quantified. Disperse Blue 1, Blue 124, and Brown 1 impaired cell viability and mitochondrial function as early as 3 h after exposure with IPEC-J2 and MPEK-BL6 cells. However, D. Blue 79.1 and Blue 291 did not have those effects. These data suggest that common disperse textile dyes can influence cell viability and mitochondrial function. This effect could be related to their chemical structure and physicochemical properties, such as size and polarity giving them differences in membrane permeability.